PEMINATAN SISWA KELAS XII SELEPAS LULUS SMA DI SEKOLAH MENENGAH ATAS NEGERI 1 KUOK - Pratiwi, Wella Rahayu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study was conducted in SMK 1 Subdistrict Kuok. The aim of this study was to determine the forms of the desired interest and attention in SMAN 1 Kuok. This study entitled